The role of institute reputation and student perceived value towards student loyalty for managing enrollments in Pakistani private HEIs - Azeem, Muhammad (2020)
In recent times, HEIs has been increasing interest in the behavioral and attitudinal intentions that aims to achieve student loyalty and finally increase the enrollments. To achieve student loyalty at higher level and increase in student enrollments, HEIs need to focus on their strategic attributes. The key strategic attributes include institute service quality, institute social responsibility, institute reputation, and student perceived value. Therefore, drawing upon the signaling theory (ST) and strategic enrollment management theory (SEMT), the mediating effect of institute reputation and the moderating role of student perceived value in this study aims to examine the influence of these strategic attributes on student loyalty. The data was collected from the 551 postgraduate students studying in eleven private HEIs of provincial capital city (Lahore) in Punjab province. The results of PLS-SEM path modeling revealed that institute service quality and institute reputation have significant relationship with student loyalty, and this same relationship significantly mediate by institute reputation. Besides, institute social responsibility has no direct significant relationship with student loyalty, but this same relationship has significantly mediate by institute reputation. Furthermore, student perceived value does not moderate the relationship between institute reputation and student loyalty. In general, the findings depicted that student loyalty can be enhanced through the examined key strategic attributes of the study. Accordingly, the study has forwarded noteworthy claims about the mediating effect of institute reputation on these variables. The study offers theoretical, methodological and practical contributions. This study also highlights the crucial role of these strategic attributes for student loyalty in private HEIs of Pakistan. Lastly, limitations and scope of further studies are also provided.